A new understanding of laser-arc plasma interaction of hybrid welding based on arc layering behaviors. (24th February 2023) - Li, Xin; Hu, Zhenlin; Lai, Jian; Gao, Wenzhong; Gong, Mengcheng; Zhang, Chen; Gao, Ming
Abstract: Current studies of laser-arc plasma interaction have been based on a single-layer structure but ignored the layering behaviors of the metal inert gas (MIG) arc, resulting in a lack of insight into some phenomena of laser-MIG hybrid welding. Here, the effects of laser power on the double-layer MIG composed of an outer plasma layer and a core metal vapor layer were investigated. The results showed that the emergence of arc layering was delayed by laser-arc plasma interaction, the time of which reached the maximum of 0.83 ms after the laser power increased to 4 kW, 1.66 times that of pure arc. Importantly, the outer layer was expanded, and the core layer was constricted by laser power, which was different from the previous argument that the arc was only compressed. An equivalent parallel circuit was proposed to reveal the current redistribution between the outer and core layers, and then the electromagnetic force was calculated to discuss the mechanism. Finally, the space-time evolution of the arc expansion and constriction phenomenon was described. These new findings explained the weld shape variations more reasonably and demonstrated the necessity to consider arc layering during laser-arc hybrid processes with a consumable electrode.